Analysis of Factors That Inhibit Students From Learning English (JEELT : JOURNAL OF EDUCATION AND ENGLISH LANGUAGE TEACHING, 2023)
This research aims to find out what factors inhibit students from learning English and what factors most dominantly inhibit students from learning English. This research is a qualitative descriptive study. Researchers used questionnaire as a data collection tool. Researchers explain the data obtained and collected through questionnaires. Based on the data results, researchers found that the factors inhibiting students from learning English were internal and external factors. The most dominant internal factor that inhibits students from learning English is attitude, while the external factor that inhibits students from learning English is the social environment. This research is also intended to introduce students to the fact that there are factors that inhibit students from learning and developing, so that this becomes part of the learning process.